Toward Technology-Based Education and English as a Foreign Language Motivation: A Review of Literature - Wei, Yi (Frontiers in Psychology, 2022)
This review made a critical attempt to examine the studies on the role of technology-based education in foreign language learners’ (EFL) academic motivation. A significant positive correlation between academic motivation and educational technology use has been approved in related studies. However, there is a dire need for studying the effect of different digital tools on learners’ motivation. The literature showed purposefulness attractiveness, effectiveness, and usefulness of digital instruments can positively affect learner motivation. There are also some reasons for increasing learner motivation in educational technology contexts, such as learners’ integration with the community, familiarizing with different societies and cultures, input flooding opportunities, engagement in academic contexts, and interaction with native speakers. In the end, the pedagogical implications are expounded to promote the learners’ grit and diminish anxiety for better performance. This review also provides suggestions for fu